Spallation target cryogenic cooling design challenges at the European Spallation Source. Issue 1 (November 2015) - Jurns, J; Ringnér, J; Quack, H; Arnold, P; Weisend, J G; Lyngh, D
Abstract: The European Spallation Source (ESS) project is a neutron spallation source research facility currently being designed and built outside of Lund, Sweden. A linear accelerator delivers a 5 MW, 2.0 GeV, 62.5 mA proton beam to a spallation target to generate fast neutrons. Supercritical hydrogen circulates through two moderators surrounding the target, and transforms the fast neutrons emitted into slow neutrons, which are the final form of useful radiation. The supercritical hydrogen is in turn cooled from a helium cryogenic plant operating at 15-20 K. The supercritical cryogenic hydrogen circuit is a dynamic system, subject to significant changes in heat load. Proper pressure control of this system is critical to assure safe operation. The interaction between the hydrogen system and helium cryoplant poses unique challenges. This paper investigates the impact of the hydrogen system constraints on operation and control of the helium cryoplant, and suggests design options for the helium circuit.